Por que as cooperativas agropecuárias e agroindustriais brasileiras estão falindo? - Crúzio, Helnon de Oliveira [UNESP] (Fundação Getúlio Vargas (FGV), Escola de Administração de Empresas de São Paulo, 1999)
Este ar tigo evidencia as contradições do Modelo Cooperativista brasileiro em relação ao Modelo Original. Trata- se de incoerências intrínsecas na formação do movimento cooperativo, nos princípios para a sua condução ideológica, bem como na regimentação e operacionalização estatutária. A partir desses desacertos, o artigo mostra as restrições para o exercício da autogestão. Também sugere mudanças nas leis cooperativistas vigentes, propícias ao exercício da participação dos associados no processo decisório.

This article evidences the contradictions of the Brazilian Cooperative System Model in relation to the Original Model. It deals with the intrinsic incoherences existing in the formation of the cooperative movement, in the principles for its ideological conduction, as well as in the regulation and statutory operationalization thereof. As from the analysis of these mistakes, the article shows the restrictions related to the exercise of self-management, and suggests changes in the cooperative system laws in force, which enable the participation of the associated parties in the decision making process.
Keywords: Cooperativismo; modelo; falência; participação; autogestão; Cooperativism; model; bankruptcy; participation; self-management